[ Implementation of Stretching Exercise to Reduce Complaints and Musculoskeletal Complaints in Orange Farmers in Bayunggede Village - Krismawati, Luh Dwi Erna; Dinata, I Made Krisna; Sutjna, Dewa Putu; Adiputra, Luh Made Indah Sri Handari; Griadhi, Putu Adiartha (Devotion : Journal of Research and Community Service, 2022)
Agricultural activities such as hoeing, cleaning grass, and fertilizing are activities that affect the work attitude of farmers. The intervention was in the form of giving Stretching Exercises with an ergonomics-based health education approach. This study aims to determine the provision of Stretching Exercises with an ergonomics-based health education approach to reduce musculoskeletal complaints and fatigue in citrus farmers in Bayunggede village. This research is an experimental study, using the same subject design with a pattern (Treatment by subject Design). This study involved 13 research samples selected at simple random. Musculoskeletal complaints were measured using a Nordic Body Map questionnaire on 4 Likert scales, work fatigue was measured using a 30-item rating scale. Measurements were taken before and after work in Period 1 and Period 2 for 3 weeks. Analysis of the data obtained begins with descriptive analysis and normality test of data with Shapiro-Wilk. Furthermore, the data with normal distribution were analyzed using paired t-test at a significance level of 5%. The results showed a significant difference (p<0.05) in musculoskeletal complaints and fatigue in Period I and Period II. By doing Stretching Exercises with an ergonomics-based health education approach, it can reduce musculoskeletal complaints by 29.53% and work fatigue by 26.97%. It can be concluded that there is a decrease in musculoskeletal complaints and work fatigue after doing Stretching Exercises with an ergonomics-based health education approach. Thus, it can be suggested to citrus farmers to manage time and work breaks well and regularly stretch.